Stereospecific ligands and their complexes - Part XIV: Crystal structure of O,O’-dipropyl ester of (S,S)-ethylenediamine-N,N’-di-2-(4-methyl)-pentanoic acid dihydrochloride - Vujić Jelena M.; Garsia-Granda Santiago; Menėndeztaboada Laura; Novaković Slađana B.; Trifunović Srećko R. (Journal of the Serbian Chemical Society, 2013)
Bidentate N,N'-ligand precursor, O,O'-dipropyl ester of (S,S)- ethylenediamine-N,N'-di-2-(4-methyl)-pentanoic acid dihydrochloride, [(S,S)- H4eddl]Cl2, was prepared and its crystal structure is given herein. It crystallizes in a P42 space group of tetragonal crystal system with a = 16.5620 (2) Å, b = 16.5620 (2) Å, c = 5.2240 (1) Å and Z = 2.